Illustrating Victorian Poetry: The Dynamics of Photographic Tableaux Vivants - Gwendoline Koudinoff (Cahiers Victoriens et Edouardiens)
This essay explores the intricate text-image relationship between Victorian poetry and their photographic illustrations by Julia Margaret Cameron, Henry Peach Robinson and Lady Hawarden. The three Victorian artists created living pictures, which are commonly referred to as tableaux vivants and which offered visual interpretations of the following poems: Idylls of the King and The Lady of Shalott by Lord Alfred Tennyson, Tristram and Iseult by Matthew Arnold and The Goblin Market by Christina Rossetti. Traditional arts such as painting, engraving and drawing attempted to illustrate the poems but the interdisciplinary nature of 19th-century photographic tableaux vivants enabled artists to associate real-based imagery with the metaphorical language of poetry. This essay therefore demonstrates how photographic tableaux vivants emulate traditional visual arts and how they exemplify a transformative and modern interpretation of Victorian poetry.